Deletion of A44L, A46R and C12L Vaccinia Virus Genes from the MVA Genome Improved the Vector Immunogenicity by Modifying the Innate Immune Response Generating Enhanced and Optimized Specific T-Cell Responses - Holgado, María Pía (2016)
MVA is an attenuated vector that still retains immunomodulatory genes. We have previously reported its optimization after deleting the C12L gene, coding for the IL-18 binding-protein. Here, we analyzed the immunogenicity of MVA vectors harboring the simultaneous deletion of A44L, related to steroid synthesis and A46R, a TLR-signaling inhibitor (MVAΔA44L-A46R); or also including a deletion of C12L (MVAΔC12L/ΔA44L-A46R). The absence of biological activities of the deleted genes in the MVA vectors was demonstrated. Adaptive T-cell responses against VACV epitopes, evaluated in spleen and draining lymph-nodes of C57Bl/6 mice at acute/memory phases, were of higher magnitude in those animals that received deleted MVAs compared to MVAwt. MVAΔC12L/ΔA44L-A46R generated cellular specific memory responses of higher quality characterized by bifunctionality (CD107a/b+/IFN-γ+) and proliferation capacity. Deletion of selected genes from MVA generated innate immune responses with higher levels of determining cytokines related to T-cell response generation, such as IL-12, IFN-γ, as well as IL-1β and IFN-β. This study describes for the first time that simultaneous deletion of the A44L, A46R and C12L genes from MVA improved its immunogenicity by enhancing the host adaptive and innate immune responses, suggesting that this approach comprises an appropriate strategy to increase the MVA vaccine potential.